Design, Computational Aerodynamic, Aerostructural, and Control Stability Investigations of VTOL-Configured Hybrid Blended Wing Body-Based Unmanned Aerial Vehicle for Intruder Inspections - Vijayanandh Raja; Ramesh Murugesan; Senthil Kumar Solaiappan; Beena Stanislaus Arputharaj; Parvathy Rajendran; Hussein A. Z. AL-bonsrulah; Deepak Thakur; Abdul Razak; Abdulrajak Buradi; Abiot Ketema (International Journal of Aerospace Engineering, 2023)
Unmanned aerial vehicles (UAVs) are gaining in popularity and sophistication in today’s modern world. UAVs are now available in a wide range of configurations. A UAV’s many applications include aerial photography and videography and target tracking. The upward-pointing propellers of some modern fixed-wing UAVs make it possible for them to take off and land vertically. Surveillance and intruder inspections are two areas where the blended wing body (BWB) configuration shines. This is because its weight is spread uniformly throughout the body, its radar signal is weaker than that of alternative configurations, and there is a relatively small amount of interference with its movement. With common design factors in mind, like vertical takeoff and landing, aerodynamic drag, and fundamental wing stability, the optimal BWB plan form for surveillance is designed. CATIA is used to finish the conceptual design of the BWB-based UAV. A fluid-structure interaction (FSI) study is carried out after the model has been examined in ANSYS Fluent. The UAV’s responsiveness is improved through simulation in the MATLAB environment after a proportional-integral-derivative-type altitude controller was developed. The results demonstrate that providing the UAV with an altitude instruction enhances its performance. Given the flexibility of the suggested BWB UAV’s design, we have decided to limit its maximum forward speed to 75 m/s and its maximum rate of vertical ascension to 50 m/s. Rapid BWB UAVs like the one seen here are quite helpful in dangerous situations.